2019
DOI: 10.22175/mmb2019.07.0022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Beef Top Sirloin Steaks of Four Quality Grades Cooked to Three Degrees of Doneness

Abstract: The objective of this study was to evaluate the impact of USDA quality grade on beef eating quality of top sirloin steaks when cooked to multiple degrees of doneness (DOD). Beef top sirloin butts (N = 60; 15/quality grade) were collected to equally represent 4 quality grades [Prime, Top Choice (modest00 to moderate100), Low Choice, and Select]. Steaks were assigned to 1 of 3 DOD: rare (60°C), medium (71°C), and well-done (77°C). Steaks were allocated to either consumer sensory analysis, trained sensory analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
4
9
2
Order By: Relevance
“…Most previous authors have reported quality grade to have no impact on the palatability traits of the gluteus medius. Olson et al (2019) reported no differences in the tenderness, juiciness, flavor, and overall liking scores of consumers when evaluating gluteus medius steaks ranging in quality grade from Select to Prime. Similar results have been reported from the 2 most recent "Beef Tenderness Surveys" that have shown no impact of quality grade on gluteus medius palatability, with steaks ranging from Prime to Select (Guelker et al, 2013;Martinez et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most previous authors have reported quality grade to have no impact on the palatability traits of the gluteus medius. Olson et al (2019) reported no differences in the tenderness, juiciness, flavor, and overall liking scores of consumers when evaluating gluteus medius steaks ranging in quality grade from Select to Prime. Similar results have been reported from the 2 most recent "Beef Tenderness Surveys" that have shown no impact of quality grade on gluteus medius palatability, with steaks ranging from Prime to Select (Guelker et al, 2013;Martinez et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Samples used in the current study were obtained from the biceps femoris removed from top sirloin butts during fabrication in a previous study, with all details related to product selection outlined by Olson et al (2019). In brief, beef top sirloin butts (N = 60; Institutional Meat Purchasing Specifications #184; North American Meat Institute, 2014) were collected with equal ratios of 4 different USDA quality grades: Select (slight 00 to slight 100 ), Low Choice (small 00 to small 100 ), Top Choice (modest 00 to moderate 100 ), and Prime (slightly abundant 00 to abundant 100 ).…”
Section: Sample Collection and Fabricationmentioning
confidence: 99%
“…The review further investigates the subjective (i.e., trained and consumer panels) and objective (i.e., physical and instrumental) measurements commonly used to quantify the appearance, palate (taste and flavor), and texture attributes of meat. The paper contributes to the growing body of reviews concerning the effect of thermal processes on the physicochemical changes and ultimate eating quality of meat (Bhat et al., 2021; Olson et al., 2019; Shen et al., 2022; Wang et al., 2022; West, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In consumer research conducted at Kansas State University, participating consumers are commonly asked about their purchasing motivators. These research studies indicated midwestern consumers placed the importance of the nutritive value of meat from 52 to 55 on a 100-point scale with 100 designated as being extremely important (Wilfong et al, 2016a(Wilfong et al, , 2016bVierck et al, 2018;Olson et al, 2019;Prill et al, 2019). In Europe, Wezemael et al (2014) reported consumers valued meat nutritional claims based on country.…”
Section: Introductionmentioning
confidence: 99%